Pocket bear - Applegate, Katherine (Feiwel and Friends, 2025)
"Born during the throes of World War I, Pocket was designed to fit into the pocket of a soldier's jacket, eyes sewn a bit higher than normal so that he always gazed upward. That way, when the soldier glanced at his pocket, he would see an endearing token of love from someone back home, and, hopefully, a good luck charm. Now, over a century later, Pocket serves as unofficial leader of Second Chances Home for the Tossed and Treasured, where stuffed toy animals are refurbished and given a fresh opportunity to be loved. He and his best feline friend, Zephyrina, known far and wide as a cat burglar, have seen it all, and then some. An unforgettable tale of bravery, loyalty, and kindness, Pocket Bear reminds us all that love comes in many forms (sometimes filled with fluff), and that second chances are always possible" --